Thriving as a Sociology Graduate. (February 2020) - Senter, Mary Scheuer; Spalter-Roth, Roberta
Students major in sociology because they want to understand social life and social change, but does wanting a meaningful career equal a large salary? As it turns out, while sociology graduates do not earn top dollars in their first year out of undergraduate school, their salaries do increase and usually double by ten years out.